Politics of risk-taking : welfare state reform in advanced democracies - Vis, Barbara (Changing welfare states., 2010)
Based on insights from prospect theory, a psychological theory of choice under risk, Vis demonstrates ably that the context in which governments find themselves (losses or gains) affects their attitude towards risk and thereby the degree and type of refor.